Implicit Expression of Information Components in the Elliptical Constructions - Zubaydullo Izomovich Rasulov (Researchparks Publishing, 2022)
The study of the problems associated with the formation of information expression in speech structures is equally relevant both theoretical and practical, and thus it is possible to identify factors that ensure the effect of communicative processes. This article analyzes the implicit expression of information components in elliptic constructions.